Analysis of Domestic Infidelity Resulting in Loss of Life SUPREME COURT DECISION NUMBER 350 K / PID / 2011 - Rogabe Rajagukguk; Frans Doni A. Pasaribu; Tarisa Alfani Siregar; Said Rizal (Warmadewa Press, 2024)
This study aims to analyse the legal implications of infidelity in the household that leads to the loss of life with a case study of Supreme Court Decision Number 350 K/PID/2011. The research focuses on how Indonesian law addresses cases where infidelity results in murder, as well as the legal challenges faced in prosecuting such cases, including the intersection of criminal law and family law. The study investigates the obstacles encountered by law enforcement, such as conflicting testimony and insufficient evidence, which complicate the prosecution of infidelity-related homicides. The study uses a normative juridical method along with a descriptive analysis of court decisions and legal texts to show differences between how the crime was categorised by the law and how it was found by the courts. The findings indicate that we can classify infidelity in this context as a factor contributing to premeditated murder, but we still face significant legal hurdles in distinguishing the criminal liability of involved parties. We offer recommendations to strengthen law enforcement's capacity, improve judicial processes, and enhance transparency in handling such cases.